Market Barrier Integrated Approach for Manufacturing Footprint Decision Support - Thillai Sivakumaran; Philipp Sprenger; Michael Toth; Michael Henke (Sustainability in Logistics and Supply Chain Management: New Designs and Strategies. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 21, 2015)
The sales potentials for automotive companies in Europe are decreasing, and emerging markets, such as the BRIC-states or the ASEAN countries, are now in the focus of European automobile manufacturer's attention. However, the governments of these high potential market states try to cap the import-rate of European cars and decrease the international competition for the local automotive industry by creating trade barriers. Car manufacturers and suppliers struggle with the planning of following a local manufacturing strategy and the related set up of regional supply chain networks. The decision finding process shows different deficits. Especially the high dynamic of the business environment and the related uncertainties are not in the scope of current planning processes. Approaches are missing which allow decision owners to evaluate the impact of changing trade barriers on the supply chain network. Derived from state-of-the-art analysis, tariff and non-tariff trade barriers will be classified in the context of opening up new automotive markets. Next to a classification, an existing simulation-based planning approach for robust manufacturing footprint decisions is extended by the consideration of the classified trade barriers.
10419/209190; https://econpapers.repec.org/RePEc:zbw:hiclpr:21
Keywords: 650; Trade Barriers; Manufacturing Footprint Decision; Supply Chain Management; Automotive Industry